Innovation in Public Participation in Policy Formulation: An Analysis of the Utilization of Digital Musrenbang Platforms - Ratnasari, Lutfiana Dwi; Hidayat, Rafiq Nur (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
Public participation is a key element of democratic governance, yet conventional Musrenbang practices in Indonesia continue to face limitations in inclusivity, transparency, and the effective conveyance of community aspirations. The digitalization of Musrenbang is expected to address these challenges by expanding access and strengthening accountability. This study aims to analyze the extent to which digital Musrenbang platforms enhance the quality of public participation and to identify the factors that influence their effectiveness. The research employs a quantitative, cross-sectional survey design involving 200 respondents, supported by secondary data, including user activity logs and official digital Musrenbang documents. Analysis was conducted using descriptive statistics, Pearson correlations, and multiple linear regression. The findings indicate that digital Musrenbang is perceived as inclusive (72%) and transparent (81%), although the effectiveness of aspiration follow-up remains limited (62%). Digital literacy and infrastructural access are the principal determinants of participation effectiveness. This study affirms that digital Musrenbang has the potential to strengthen technology-based participatory democracy, if user capacity and accountable follow-up mechanisms are adequately supported.